Synthesis and characterisation of ion-implanted epoxy composites for X-ray shielding - Noor Azman, N.; Siddiqu, S.; Ionescu, M.; Low, Jim (Oxford University Press, 2012)
The epoxy samples were implanted with heavy ions such as tungsten (W), gold (Au) and lead (Pb) to investigate the attenuation characteristics of these composites. Near-surface composition depth profiling of ion-implanted epoxy systems was studied using Rutherford Backscattering Spectroscopy (RBS). The effect of implanted ions on the X-ray attenuation was studied with a general diagnostic X-ray machine with X-ray tube voltages from 40 to 100 kV at constant exposure 10 mAs. Results show that the threshold of implanted ions above which X-ray mass attenuation coefficient, µm of the ion-implanted epoxy composite is distinguishably higher than the µm of the pure epoxy sample is different for W, Au and Pb.